Legitimizing policing practices: a study of stakeholder perceptions of police trustworthiness, effectiveness and relationship with the community. (15th January 2021) - Watson, Danielle; Boateng, Francis D.; Miles-Johnson, Toby
ABSTRACT: In an attempt to better meet the needs of the communities, the Tuvalu Police Service (TPS) commissioned a survey to investigate stakeholder perceptions of police service provision across its nine islands. This paper presents the findings of the survey and examines the responses of community residents ( N = 1896) to determine public perceptions of police trustworthiness, police effectiveness and the relationship between the TPS and the community. The results suggest community residents have positive views of the TPS as service providers. However, there are mixed views about police trustworthiness and the ability of TPS officers to respond to crime. We examine how community policing in Tuvalu shapes public perceptions of police, thus building on a small body of scholarship examining perceptions of police in the developing world. As such, this study contributes new knowledge regarding public perceptions of the TPS and police fairness in Tuvalu, an area hitherto under researched in the policing literature examining policing in the South Pacific. It also informs police practice regarding improving policing in communities where justice systems are dominated by cultural practices involving community elders and chiefly councils.